2007
DOI: 10.2337/db06-0860
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes of Transcription Factor 7–Like 2 (TCF7L2) Gene and Its Upstream Region Are Associated With Type 2 Diabetes and Age of Onset in Mexican Americans

Abstract: 1TCF7L2 acts as both a repressor and transactivator of genes, as directed by the Wnt signaling pathway. Recently, several highly correlated sequence variants located within a haplotype block of the TCF7L2 gene were observed to associate with type 2 diabetes in three Caucasian cohorts. We previously reported linkage of type 2 diabetes in the San Antonio Family Diabetes Study (SAFADS) cohort consisting of extended pedigrees of Mexican Americans to the region of chromosome 10q harboring TCF7L2. We therefore genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 16 publications
4
74
0
2
Order By: Relevance
“…Five single nucleotide polymorphisms (SNPs) (rs12255372, rs7903146, rs7901695, rs11196205, and rs7895340) within the LD block also showed similarly robust associations with type 2 diabetes (6). Further studies in other European populations, African Americans, Mexican Americans, and Asian Indians confirmed the strong associations with an estimated population attributable risk of 17-28% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Several genome-wide association studies independently confirmed the strong associations of SNP rs7903146 in the TCF7L2 locus with type 2 diabetes (23)(24)(25)(26).…”
mentioning
confidence: 59%
“…Five single nucleotide polymorphisms (SNPs) (rs12255372, rs7903146, rs7901695, rs11196205, and rs7895340) within the LD block also showed similarly robust associations with type 2 diabetes (6). Further studies in other European populations, African Americans, Mexican Americans, and Asian Indians confirmed the strong associations with an estimated population attributable risk of 17-28% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Several genome-wide association studies independently confirmed the strong associations of SNP rs7903146 in the TCF7L2 locus with type 2 diabetes (23)(24)(25)(26).…”
mentioning
confidence: 59%
“…Similarly, this polymorphism was found associated with diabetes in several works carried out in admixed populations from other Latin American countries (9,(23)(24)(25)28,29,31,32). However, Barros and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among Latin American countries there are only reports on the association of TCF7L2 polymorphisms and T2DM from Colombia (23), Brazil (24)(25)(26)(27)(28) and Mexico (9,(29)(30)(31)(32). Latin American populations are characterized by high socioeconomic and genetic heterogeneity with varying degrees of ancestral population proportions from country to country, thus more studies are needed exploring the basis of T2DM susceptibility from these mixed populations.…”
Section: Tcf7l2 Polymorphisms and Type 2 Diabetes Riskmentioning
confidence: 99%
“…35) and has been replicated in subsequent studies in many different ethnicities. [8][9][10][11][12][13][14][15][16] The association of other newly emerged GWAS loci, such as IGF2BP2, CDKAL1, CDKN2A/B, HHEX, SLC30A8 and KCNJ11, was replicated in Japanese; 17,18 IGF2BP2, SLC30A8, HHEX, CDKAL1, CDKN2A/B and FTO in Asians from Hong Kong and Korea; 19 IGF2BP2, CDKAL1, CDKN2A/B, HHEX and SLC30A8 in Han Chinese; 20 and IGF2BP2, PPARG2 and FTO in Indian Sikhs. 21 More recently, a meta-analysis of three large GWA studies by the Diabetes Genetics Replication and Meta-analysis (DIAGRAM) Consortium identified six additional T2D loci (NOTCH2, THADA, ADAMTS9, JAZF1, CDC123/CAMKID and TSPAN8/LGRS) to be strongly associated with increased susceptibility to T2D with modest ORs (1.15À1.3).…”
Section: Introductionmentioning
confidence: 96%